ADOLESCENT INTERACTION IN COMMUNITY CULTURE AND LANGUAGE 5:0 - Dieni, Asmira; Sari, Siti Mayang (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Descriptive qualitative research with the case study method is a research approach used to gain an in-depth understanding of a particular phenomenon, event, or case in a real context. Researchers observe phenomena in their natural environment without manipulation. The research seeks to understand the perspectives and experiences of participants. Data are collected through interviews, observations, documents, or artifacts. Researchers describe the data in depth, providing an overview of emerging themes or patterns, such as: How adolescents in a particular community practice local languages ​​in everyday conversation. The role of local culture in shaping adolescents' social identities at school. The influence of peer groups on the use of slang in social media.Today's teenagers often use sentences in language and culture that resemble foreign languages ​​or are called "slang", in society in general teenagers communicate with peers in a language that is less understood by adults. This current civilization gives character to the next generation, negative impacts but the need for encouragement and motivation from parents in directing teenagers to better relationships. Interaction between teenagers in communities in Indonesia is rife with culture and everyday language, perhaps in an academic, research or social context it could be a finding that the language used by teenagers today leads to bullying. Teenagers play an important role in shaping and maintaining the dynamics of society. They participate in cultural practices, social activities, and local events, which often bridge tradition and modernity.